Level of Community Compliance About Health Protocols and Influencing Factors in Panceran Hamlet, Ngancar Village Kediri Regency - Dian Fery Handrianti; Anggraeni, Novita (Universitas STRADA Indonesia, 2022)
The spread of the Covid-19 virus has been increasing lately. The high rate of transmission has made every country appeal to the public to reduce activities outside the home. We hope that by implementing health protocols during the Covid-19 pandemic according to the government's recommendations, we can help stop the spread of various kinds of bacteria or viruses, including the Covid-19 Virus. However, until now there are still many people who still do not comply with health protocols properly. The factors that influence compliance include knowledge, attitudes, support and self-motivation. The purpose of this study was to analyze the factors that influence community compliance with health protocols in Panceran Hamlet, Ngancar District, Kediri Regency. The research method used in this study is a quantitative method. This study used a cross-sectional design. The population in this study was the community of Panceran hamlet, Ngancar village with a sample of 50 respondents. The statistical test used for data analysis in this study was a simple linear regression test with a degree of confidence = 0.05. The results showed that there was an influence of the knowledge factor with the level of community compliance with health protocols of 60% with a t-count value of 8.483. The influence of self-motivation factors with the level of community compliance with health protocols is 89.5% with a t-count value of 20.249. The influence of family support factors on the level of community compliance with health protocols is 68.9% with a t-count value of 10.306. The influence of the attitude factor with the level of community compliance with health protocols is 92.5% with a t-count value of 24,268. Thus it can be concluded that knowledge, self-motivation, family support and character are factors that have an influence on a person's level of compliance.